TEACHING MATHEMATICAL FUNCTIONS WITH MATLAB - SZABO, Tibor; MOLNAR, Jozef; ZITNY, Rastislav (Trends in education, 2008)
In teaching mathematics adequate types of informational and communicational technologies applications can be used. The usage of such technologies may improve the teaching process and the process of learning. It can help to develop the students extasciiacute thinking/ideal and creative activities. The paper deals with the possibilites of usage of Matlab program in mathematics, concrete in teaching mathematic functions of two variables. The article defines it as a teaching aid that is able to draw graph functions of two variables and their tactile/tangential plane that helps us to view the importance of partial derivation.
Keywords: Matlab; function of two variables; graph function of two variables; visualization; tactile plane